Acquiring Knowledge the Quilombola Territory of the Jambuaçu River through the Games - Araújo, Jasmine Priscyla Leite de; Alcântara, Ana Carolina Monteiro dos Santos de; Barros, Fabrício José Brito; Cavalcante, Gervásio Protásio dos Santos; Castro, Bruno Souza Lyra; Neto, Miércio Cardoso de Alcântara; Nunes, Arthur Tavares (International Journal for Innovation Education and Research, 2021)
This game aims to become a didactic-pedagogical tool to facilitate the interaction and transmission of history, culture and some traditional knowledge of quilombola community living in the Quilombola Territory of the Jambuaçu River, located in the municipality of Mojú, state of Pará, to be applied to the students of the local schools and students of the School of Application of the Federal University of Pará. It also aims to boost the interaction between these different worldviews, through the joint elaboration between quilombola researchers, community members of the Quilombola Territory of the Jambuaçu River and the others researchers